Molecular Regulation of Neutrophil Apoptosis and Potential Targets for Therapeutic Strategy Against the Inflammatory Process - Hofman, Paul (Current Drug Targets - Inflammation & Allergy, 2004)
The balance between polymorphonuclear leukocytes (PMNL) apoptosis and necrosis in inflamed tissues is an important determinant of the degree of tissue injury. To prevent senescent PMNL from releasing their toxic contents into surrounding tissues, these cells become apoptotic and are then internalized by tissue macrophages. PMNL apoptosis and subsequent ingestion by macrophages are the major mechanisms for clearing PMNL that have been recruited to the inflamed sites and thus for promoting resolution of the inflammation. PMNL have a short half-life that is extended at the inflamed site by pro-inflammatory cytokines including Granulocyte-Macrophage Colony-Stimulating Factor (GM-CSF), Interleukin-8 (IL-8), Gro- α, and they contact with the bacterial cell walls containing lipopolysaccharides (LPS). Conversely, antiinflammatory cytokines, such as IL-10, accelerate the apoptosis of LPS-activated PMNL. Spontaneous PMNL apoptosis does not require Fas ligation but involves proteolytic cascades -caspases (particularly caspases 3 and 8), calpains and the proteasome-that activate kinases, e.g. caspase 3-mediated activation of protein kinase C-δ, dissociate actin-binding proteins from filamentous actin, and participate in cell surface as well as nuclear morphological transformations. Members of the Bcl-2 protein family, Mcl-1 and A1, are involved in the regulation of PMNL apoptosis. Cell surface receptors and protein kinases, particularly mitogen-activated protein kinases (MAPK), also play critical roles in transducing the signals that result in PMNL apoptosis or extended survival. A growing understanding of the mechanisms regulating leukocyte apoptosis and of the molecules mediating safe phagocytic clearance of dying cells may yield new insights into the pathogenesis of inflammatory diseases. In this regard, therapeutic strategies to resolve chronic inflammation could usefully target PMNL. This review summarises current knowledge on the molecular mechanisms and components of PMNL apoptosis.
Keywords: signal transduction